High Flow Nasal Cannula versus Nasal Continuous Positive Airway Pressure for Primary Respiratory Support in Preterm Infants: A Prospective Randomized Study - Demirel, Gamze; Vatansever, Binay; Tastekin, Ayhan (American Journal of Perinatology, 2019)
Objective This study compares high flow nasal cannula (HFNC) with nasal continuous positive airway pressure (nCPAP) within the first hour of life as the primary respiratory support in neonates of ≤32 weeks of gestational age.Study Design This prospective, randomized study was conducted in infants with a gestational age of ≤32 weeks who had spontaneous respiration. HFNC or nCPAP was used as a first line respiratory support after admission to intensive care unit. Primary outcome was primary treatment failure. Secondary outcomes were duration of noninvasive respiratory support and oxygen treatment, maximum FiO2 level, length of hospital stay, intubation rate, rates of respiratory distress syndrome, pneumothorax, and bronchopulmonary dysplasia. Subgroup analysis was performed for infants ≤28 weeks of gestational age.Results We enrolled 107 infants, 53 in HFNC and 54 to nCPAP group. There was no difference in primary outcome between the two groups. There was no difference between the groups in aspect of secondary outcomes.Conclusion HFNC and nCPAP have no significant differences as a primary mode of respiratory support in preterm infants, in the time to wean off the devices and oxygen support, respiratory distress syndrome and bronchopulmonary dysplasia incidence, hospitalization duration, and rates of complications of prematurity.
Keywords: high flow nasal cannula; nasal continuous positive airway pressure; preterm infant; respiratory distress